Comunicação pública e meio ambiente: a cobertura da atuação do MPF no RN contra a ocupação de áreas de preservação por empresas salineiras - Melo, André Wolmer de (2022)
The Brazilian state of Rio Grande do Norte concentrates 95% of the salt production in the country. This secular activity moves the economy, politics and society of the known Costa Branca ("White Coast") region, in the semi-arid region of the state. However, studies by environmental protection agencies indicate a series of environmental damages caused by the maintenance of salt piles in Permanent Preservation Areas (APPs in Portuguese). This research consists of a quali-quantitative analysis of the coverage on the actions of the Federal Prosecution Office in the Rio Grande do Norte (MPF/RN) in favor of the removal of irregular salt piles, in 2019, by blogs, portals and digital news agencies. It includes the quantification of the space dedicated to the theme and the approaches addressed, including taking into account the presence of the theoretical principles of Environmental Journalism. We also seek to understand how the position expressed by the MPF/RN was portrayed by the media and which voices were more prominent. To this end, the main concepts of the sociologist Pierre Bourdieu about social structures and power struggles were applied to the Content Analysis methodology, with emphasis on the social fields involved and their agents and institutions. The study shows that the digital media had, for the most part, a passive posture and repeated the contents disseminated by MPF/RN's press office, leading to an emphasis on the environmental and juridical fields in the informative discourse that reached the readers. Nevertheless, a great part of the news approached the socio-environmental issues in a fragmented and superficial way, distancing itself from the proposal of engaged Environmental Journalism. The analysis of the mentions and sources used in the texts demonstrates that the intersection between the environmental, scientific and juridical fields - represented mainly by the MPF/RN - prevailed over the discourse coming from the economic field (which was supported by the political field).